Wood volume coefficient estimation of the wood-savanna of Brasília - Encinas, José Imaña; Monti, Estevão Ribeiro (Pesquisa Agropecuaria Brasileira, 2014)
This article determines the volume coefficient for the wood volume in the wood-savanna region of Brasília, Brazil. The form factor computed by means of the accurate cubing provided an average value of 0.6. The volume coefficient obtained from 15 piles was 0.364.
Keywords: wood volume coefficient; forest mensuration